Foliar selenium fertilization alters the content of dietary phytochemicals in two rocket species - Schiavon, Michela; Nardi, Serenella; Pilon-Smits, Elizabeth A. H.; Dall’Acqua, Stefano (Frontiers in Plant Science, 2022)
Biofortification is the process that aims to enrich crops in micronutrients and valuable compounds. Selenium (Se) biofortification has particularly attracted increasing interest in recent times due to the growing number of individuals suffering from Se deficiency. Selenate and selenite are the Se forms most frequently administered to crops. In this study, Se was applied foliarly as selenate at 2.5, 5 or 10 mg per plant to two rocket species, Diplotaxis tenuifolia and Eruca sativa, grown in soil and the effects in terms of Se enrichment and content of primary and secondary metabolites were comparatively analyzed. We also compared our results with those obtained previously when selenate was supplied to the same species in hydroponics by addition to the nutrient solution. In most cases, the results were opposite. In E. sativa, foliar Se treatment was more effective in promoting Se accumulation, sulfur (S), cysteine, and glucosinolates. No significant effect of Se was evident on total phenolics content, but there were for individual phenols. Among amino acids, the content of proline was increased by Se, perhaps to counteract osmotic stress due to high Se accumulation. In D. tenuifolia, the content of S and cysteine decreased under Se treatment, but the amount of glutathione was steady, suggesting a preferred assimilation of cysteine toward the synthesis of this antioxidant. Consistent, the content of methionine and glucosinolates was reduced. The content of total phenolics was enhanced only by the low Se dosage. In both species, selenocysteine (SeCys) was identified, the content of which was higher compared to plants grown hydroponically. Concluding, most metabolic differences between rocket species were observed at high Se supplementation. Low Se foliar fertilization was effective in enriching rocket in Se without affecting other phytochemicals. However, the Se dosages sufficient for biofortification could be even lower, as the Se concentration in rocket treated with 2.5 mg Se per plant was still very high and the edible part should not be eaten undiluted. Also, a single method of Se supplementation doesn’t appear to be optimal for all plant species or the same species, as the metabolic responses could be very different.